The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1177/1010428317694536
|View full text |Cite
|
Sign up to set email alerts
|

Crocetin shifts autophagic cell survival to death of breast cancer cells in chemotherapy

Abstract: The chemotherapy with fluorouracil is not always effective, in which some breast cancer cells may survive the fluorouracil treatment through enhanced autophagy. Crocetin is the major constituent of saffron, a Chinese traditional herb, which has recently found to have multiple pharmacological effects, including anticancer. However, the effects of Crocetin on the outcome of fluorouracil therapy for breast cancer have not been studied. Here, we showed that fluorouracil treatment inhibited the growth of breast can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
0
4
1
Order By: Relevance
“…We aimed to study the possible involvement of the mTOR pathway in the protective effects of Saffron. Studies have been performed on the effect of Crocin in liver cancer [ 58 ] and Crocetin in breast cancer [ 59 ] and their effects on autophagy have been reported, but the results of our study showed that Saffron has no effect on mTOR or p-mTOR expression in skin flap tissue. We did not observe significant mTOR and p-mTOR changes between groups.…”
Section: Discussioncontrasting
confidence: 73%
“…We aimed to study the possible involvement of the mTOR pathway in the protective effects of Saffron. Studies have been performed on the effect of Crocin in liver cancer [ 58 ] and Crocetin in breast cancer [ 59 ] and their effects on autophagy have been reported, but the results of our study showed that Saffron has no effect on mTOR or p-mTOR expression in skin flap tissue. We did not observe significant mTOR and p-mTOR changes between groups.…”
Section: Discussioncontrasting
confidence: 73%
“…Rai et al (48) demonstrated that resveratrol was able to chemosensitize doxorubicin in combination through suppressing Beclin1 in breast cancer cells. Zhang and Li (49) reported that crocetin may increase autophagic cell death via the inhibition of the expression of Beclin1 in breast cancer cells during fluorouracil treatment. However, few reports have demonstrated an association between Beclin1 and paclitaxel treatment in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that the therapeutic effects of crocetin against some types of cancers, including breast cancer, have been pointed out [ 47 , 48 , 54 56 , 66 69 ]. Crocetin acts in a dose-dependent manner in in vitro models [ 47 , 55 , 67 , 68 ]. Oral administration of crocetin has been employed in research on mice aimed to investigate its effects against retinal damage [ 70 ] and tumour growth [ 56 , 69 ].…”
Section: Discussionmentioning
confidence: 99%